2016
DOI: 10.1089/met.2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Metabolic Syndrome and Cognitive Abilities in U.S. Adolescents

Abstract: Metabolic syndrome was associated with impaired reading, working memory, and attention among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“… Bae and colleagues (2017 ) found gender differences in individual MetS components, which were differentially associated with risk of nonamnestic mild cognitive impairment. MetS has been associated with impaired reading, working memory, and attention among adolescents ( Rubens et al., 2016 ). Adverse relationship between Digit symbol test scores and increasing numbers of MetS constituents has also been reported ( Tsai et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… Bae and colleagues (2017 ) found gender differences in individual MetS components, which were differentially associated with risk of nonamnestic mild cognitive impairment. MetS has been associated with impaired reading, working memory, and attention among adolescents ( Rubens et al., 2016 ). Adverse relationship between Digit symbol test scores and increasing numbers of MetS constituents has also been reported ( Tsai et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjusting for putative confounders, the association with TG did not remain significant [ 20 ]. On the contrary, data from the NHANES study showed no association between cognitive performance measured with the digit span task (a measure of working memory) and exceeding the MetS cut point or being in the highest or lowest quartiles for HDLc or TG, respectively [ 22 , 24 ]. Likewise, studies in adults are also conflicting (for review see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no association between the flanker task variables and insulin resistance measured by HOMA-IR was found. Previous studies in youth have used fasting glucose as a measure of glucose metabolism, and have likewise not observed any associations with executive functions [ 20 , 22 , 24 ]. In adults, an association between diabetes and cognitive impairment (including dementia) has been well established (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS prevalence in developing countries ranges from 20% to 50% in obese Mexican adults 8 , children, and adolescents with a 62% MS prevalence rate 9 . In addition, studies with US adolescents have shown that the presence of MS generates a decrease in cognitive abilities and skills 10 that leads to the urgent need to seek predictors and risk factors that are associated with metabolic alterations 11 and to a more practical detection of MS 12 .…”
Section: Introductionmentioning
confidence: 99%